Prognosis of IgA nephropathy patient with proteinuria remission by supportive therapy: cohort from screening failed Chinese patients in TESTING study - Yingman Guo; Sufang Shi; Jinghong Zhao; Caili Wang; Zhangsuo Liu; Shuxia Fu; Nan Chen; Guisen Li; Lihua Wang; Zhaohui Ni; Haitao Zhang; Lingyun Lai; et al. (Renal Failure)
Background During the run-in phase of the TESTING study, approximately half of patients with IgA nephropathy (IgAN) were excluded due to proteinuria below 1 g/24 h after intensive supportive therapy. The long-term prognosis of these patients needs further investigation.Methods 112 screening failed patients in the TESTING study from 10 centers in China were enrolled in this retrospective study. The prognosis of 88 patients, who were excluded because of proteinuria below 1 g/24 h, was analyzed by Landmark Kaplan-Meier analysis. The composite kidney endpoint was defined by a ≥ 50% reduction in eGFR, ESKD (eGFR <15 mL/min per 1.73 m2), chronic dialysis for at least 6 months, or renal transplantation.Results In total, 88 patients were excluded due to proteinuria less than 1 g/24 h. During the follow-up, 73/88 (83.0%) patients received renin-angiotensin system blocker. 72/88 (81.8%) had stable proteinuria remission and did not receive immunosuppressive therapy (IST), and 16/88 (18.2%) received IST because of a relapse of proteinuria. Landmark Kaplan–Meier analysis revealed that, the kidney survival from dialysis or composite kidney outcome of these excluded patients with IST was similar to those without IST during the early stages of follow-up (dialysis, before 60 months, p = 0.778; composite kidney outcome, before 48 months, p = 0.862); whereas the risk for dialysis of patients receiving IST was significantly higher than those without IST after 60 months (OR = 11.3, p = 0.03). Similarly, the risk for the composite kidney outcome of patients receiving IST was also significantly higher than those without IST after 48 months (OR = 5.92, p = 0.029).Conclusions IgAN patients who maintained a persistent remission of proteinuria after intensive supportive therapy had a much better long-term kidney outcome than those who experienced a relapse of proteinuria and needed IST.